Encapsulation of dodecyl trimethyl ammonium bromide-modified montmorillonite clay platelets in poly(methyl methacrylate-co-ethyl acrylate) particles. (December 2017) - Xu, Jingshui; Chen, Denglong; Chen, Qinghua; Zhang, Zhong; Hu, Xionglong; Bai, Xin
Montmorillonite (MMT) clay platelets were successfully encapsulated in poly(methyl methacrylate- co -ethyl acrylate) [poly(MMA- co -EA)] matrix by an in situ suspension polymerization, and evaluated for their plugging behaviors in single-sand pack tube models. Swelling behaviors of the poly(MMA- co -EA)/MMT nanocomposites in various salinity water were also investigated. Results showed that the poly(MMA- co -EA)/MMT nanocomposites had a spherical morphology and their particle sizes mainly range from 10 to 120 µm by scanning electron microscopy (SEM) analysis. X-ray diffraction indicated that the existing of MMT layers in the polymer matrix was mainly in exfoliated form; this was consistent with transmission electron microscopy analysis. The thermal stability of poly(MMA- co -EA)/MMT nanocomposites were effectively improved after adding the MMT by thermogravimetric analysis. Furthermore, the selected nanocomposites containing MMT (1.0 wt%) provided an effective plugging in sand pack tubes of high permeability, and plugging rate was up to approximately 85.0%.